Iron and Steel Division - Stability Relations of Calcium Ferrites: Phase Equilibria in the System 2CaO-Fe2 O3-FeO-Fe2O3-Fe2O3 Above 1135° C - Bert Phillips; Arnlf Muan (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
The quenching technique has been used for- a study of phase velntiorzs within the composition triangle 2CaO.Fe2O3-FeO.Fe2O3 Fe2O3 of the system Ca-Fe-O. Desired total compositions of sanzples were attained by weighing of starting materials in required proportions and keeping them in sealed 80 pct Pt 20 pct Rh tubes during equilibration .runs. The liquidus surface has been delineated. the existence of two ternary compounds has been established, and seven ternary inwariant situations have been determined. ONE unit within the research program on refractory oxides in progress in our laboratories is the study of phase relations in the system Ca-Fe-Si-O. The present paper deals with the ternary system 2CaOFe2O3-FeO.Fe2O3-Fe2O3, which is only a small part of the enormously complex quaternary system. Many of the phases occurring in iron ore sinter products have compositions which can be closely approximated within this ternary system, and a knowledge of stability relations existing among these phases may be expected to be a useful guide for improving sintering operations. Two fundamentally different experimental approach es are commonly used in studies of systems containing iron oxides, both permitting control of the oxidation state of Fe. One method consists in keeping constant the oxygen partial pressure of the gas phase in equilibrium with condensed phases (liquid and crystalline). In the other method, which is the one used in the present investigation, the total composition of condensed phases is kept essentially constant by keeping the samples in a gas-tight container. The details of this experimental procedure will be described in a later section. PREVIOUS WORK Extensive studies of phase relations in the bounding binary system FeOFe2O3-Fe2O3 have been reported by Greig, Posnjak, Merwin, and Sosman,' by Darken and Gurry,2, 3 and recently by Phillips and Muan.4 A diagram summarizing the results of these studies is shown in Fig. 1. Particular attention is